Biosimilar monoclonal antibodies in lymphoma: a critical appraisal. Issue 5 (May 2015) - Rioufol, Catherine; Salles, Gilles
<x xml:space="preserve">Abstract</x> Rituximab, an anti-CD20 monoclonal antibody, revolutionized the treatment of lymphoma. Although newer generation anti-CD20 monoclonal antibodies are being examined, patent expiries and patient demand have fueled the development of rituximab biosimilars. The development of such agents is both an important and difficult undertaking. By definition, although they aim to have safety and efficacy comparable with their reference agents, biosimilars are not exact replicas of those agents, and small changes in nonclinical and preclinical properties may ultimately affect in vivo activity. Consideration must be given to the complex mechanisms of action, sensitive patient populations that may be treated, and appropriate clinical trial endpoints. Furthermore, extrapolation of indications is multifaceted, deserving close examination. This review represents a critical look at biosimilars in lymphoma and their safety, efficacy and long-term effects on patient outcomes.